DIABETIC NEUROPATHIC PAIN - Reza Rachmantoko; Zamroni Afif; Dessika Rahmawati; Rodhiyan Rakhmatiar; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Diabetic Neuropathy is the most common complication from diabetes, which experienced in almost 90% diabetes patient. Evenly pain is one of the most common symptoms of diabetic neuropathic, but the pathophysiology mechanism of pain is not clearly known. The hyptosesis of toxicity of hyperglycemia on development of pain complication has been widely accepted globally, but there is other proposed hypothesis. Basic concept in management of painful diabetic neuropathic is exclusion of the other cause of painful peripheral neuropathy, improving glycemic control for prophylaxis therapy and medication use for alleviating pain. The first choice drug of therapy for alleviating pain are anticonvulsant, like pregabalin and gabapentin, and antidepressant, mainly that work on inhibiting serotonine and noradrenaline reuptake. In conclusion, the better understanding of painful diabetic neuropathic underlying mechanism can help to find a better management that improving the guideline quality in optimalizing pain control.